Die Rolle des Internets als Informationsbeschaffungsmedium in Banken - Peter Roßbach (Frankfurt School of Finance & Management, 2009)
Subject of the study presented in this paper is the analysis of the relevance of the Internet as an information source in German banks. The results show, that today the Internet is indeed the most important information source for many types of information used in the business processes of banks. Especially sources free of charge are not only used widely, they are moreover evaluated very high in quality. It is argued, that attitude and behavior are mainly influenced by psychological and sociological factors. Finally, it is stated, that due to the loss of control over parts of the input factors it is necessary for the banks to actively incorporate the Internet into the quality management processes.
urn:nbn:de:101:1-200907211353
Keywords: 330; Information Search Behavior; Internet; Banks; Psychology; Sociology